The Core when Strategies are Restricted by Law - Bergstrom, Theodore C. (Review of Economic Studies, 1975)
Journal Article The Core when Strategies are Restricted by Law Get access Theodore C. Bergstrom Theodore C. Bergstrom Washington University, St Louis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 2, April 1975, Pages 249–257, https://doi.org/10.2307/2296532 Published: 01 April 1975